2013
DOI: 10.1371/journal.pgen.1003887
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Proliferative History in Lymphocyte Development with Cre-Mediated Sister Chromatid Recombination

Abstract: Tracking and isolating live cells based on their proliferative history in live animals remains a technical challenge in animal studies. We have designed a genetic marking system for tracking the proliferative frequency and history of lymphocytes during their development and homeostatic maintenance. This system is based on activation of a fluorescent marker after Cre-dependent recombination between sister chromatids at a specially designed tandem loxP site, named Tlox. We have demonstrated the utility of the Tl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Because the Vγ1.1/Vδ6.3 subset develops and expands perinatally (Zhang, Dai et al 2013), we sought to determine the dynamics of IL-13 production throughout the life of Id3 knockout mice. By examining neonatal mice (6 days old), we were able to determine whether T cells gain IL-13 competency in the thymus early in life, prior to recirculation of peripherally derived effector T cells.…”
Section: : Resultsmentioning
confidence: 99%
“…Because the Vγ1.1/Vδ6.3 subset develops and expands perinatally (Zhang, Dai et al 2013), we sought to determine the dynamics of IL-13 production throughout the life of Id3 knockout mice. By examining neonatal mice (6 days old), we were able to determine whether T cells gain IL-13 competency in the thymus early in life, prior to recirculation of peripherally derived effector T cells.…”
Section: : Resultsmentioning
confidence: 99%
“…Our previous studies have demonstrated that the Tlox system could be used to track lymphocyte proliferation in combination with appropriate Cre transgenes (25). Cre-mediated recombination between a paired Tlox sites on sister chromatids occurs exclusively during cell cycle, resulting in permanent activation of the tdTomato marker from the Tlox reporter among a fraction of the daughter cells ( Figure 1A).…”
Section: Tlox/ox40cre System Tracks a Population Of Post Expansion Tregsmentioning
confidence: 99%
“…(2) tdTomato positive cells come from tdTomato negative cells but not vice versa. 3Because the labeling frequency cannot be higher than 25% per cell cycle (25), both tdTomato positive and negative cells can be generated from the non-labeled founder cells. (4) Assuming Cre activity remains stable during clonal expansion, the frequency of non-labeled descendants reduces after each cell cycle, as such tdTomato labeled fractions will become the dominant population within the expanded clones.…”
Section: Supplementalmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 3: the offspring of a label-positive cell experience asymmetric label-loss. There are genetic constructs where, on division, labels are lost asymmetrically [73]. That is, if a label-positive cell divides in two and one of its two offspring loses its label, then the other does not.…”
Section: Assumptionmentioning
confidence: 99%